SHG banking: A financial technology for reaching marginal areas and the very poor : NABARD's program of promoting local financial intermediaries owned and managed by the rural poor in India - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2001)
Reaching 100 million of India?s rural poor with savings and credit by 2008: This is NABARD?s goal through its SHG banking program, leveraging the strength of the formal banking system and the flexibility of informal self-help groups in providing adequate financial services to the rural poor. Through NGOs, government agencies and banks, vast numbers of self-help groups have been established in recent years: as selfreliant autonomous local financial intermediaries. 85% of the members are women; they have proven to be the better savers, borrowers and investors. Most of them are from the lowest castes and other disadvantaged groups. The SHGs mobilize their own savings, transform them into loans to members and plow their earnings from interest income back into equity. On that basis, SHGs and banks enter into commercial relations of mutual benefit, with low bank and client transaction costs and negligible risks. In the absence of interest rate restrictions and with repayment rates >99%, SHG banking is highly profitable – a message that has convinced hesitant bank managers in increasing numbers. SHGs are now forming local networks with their own cooperative financial institutions. The program has turned into a social movement, with high expansion rates in recent years. Fuelled by competence and enthusiasm at all stakeholder levels, it expands rapidly throughout India, including marginal and tribal areas. It is probably the world?s largest and most successful microfinance program for the rural poor – outstanding in its emphasis on self-reliance and local autonomy of the very poor. Here are some outreach and performance figures (Dec. 2000): - 364,000 SHGs established as autonomous financial intermediaries; - 5.8 million SHG members - 30 million rural poor covered as household members - 194,500 SHGs credit-linked to banks - 380 banks and 8000 bank branches involved as bank partners - Non-performing bank loans to SHGs: 0% - 750 NGOs and many GOs involved as social mobilizers and facilitators. A TAG to disseminate SHG banking in Asia – reaching hundreds of millions: NABARD is now facing the combined challenges of how to disseminate the approach throughout India and the region; and how to continue financing the incremental costs of technical and financial assistance to the participating agencies. This calls for a coordinated donor effort: with the objective of strengthening and mainstreaming the program in India and disseminating it throughout the Asia region. IFAD, together with ADB and other donors, might play a key role: promoting financial services that benefit hundreds of millions of the rural poor in Asia. As a first step, a feasibility study is suggested in preparation of a TAG for assessing, packaging and mainstreaming SHG banking innovations and disseminating them throughout India and the Asia region. Cooperating partners may include ADB, SDC, GTZ, NABARD and APRACA.
Keywords: 330